2004
DOI: 10.1038/sj.bjp.0705631
|View full text |Cite
|
Sign up to set email alerts
|

Na+/H+ exchange inhibition attenuates left ventricular remodeling and preserves systolic function in pressure‐overloaded hearts

Abstract: 1 Cardiac hypertrophy is a homeostatic response to elevated afterload. Na þ /H þ exchanger (NHE) inhibition reduces the hypertrophic response in animal models of left ventricular hypertrophy (LVH) and myocardial infarction. We examined the effect of chronic treatment with cariporide, a selective inhibitor of Na þ /H þ exchanger isoform 1 (NHE-1), on left ventricular (LV) systolic and diastolic function under pressure overload conditions. 2 Male CD-1 mice were randomized to receive either a control diet or an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…A variety of stimuli can lead to cardiac hypertrophy, including elevated arterial blood pressure, myocardial infarction, valvular heart disease, and cardiomyopathy (23). NHE1 inhibition has been proven to prevent or induce regression of hypertrophy in several models of cardiac hypertrophy (6,7,18,19,32,35,40). However, it is still largely unknown by what mechanism(s) elevated NHE1 propagates hypertrophic injury, although a number of pathways have been proposed (20,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of stimuli can lead to cardiac hypertrophy, including elevated arterial blood pressure, myocardial infarction, valvular heart disease, and cardiomyopathy (23). NHE1 inhibition has been proven to prevent or induce regression of hypertrophy in several models of cardiac hypertrophy (6,7,18,19,32,35,40). However, it is still largely unknown by what mechanism(s) elevated NHE1 propagates hypertrophic injury, although a number of pathways have been proposed (20,44).…”
Section: Discussionmentioning
confidence: 99%
“…Hearts were fixed in 10% buffered formalin overnight, embedded in paraffin, and serially sectioned into 5-m slices (6,40). Samples were stained with hematoxylin and eosin (H & E) to evaluate gross morphology and cross-sectional area (CSA) or with picrosirius red to assess fibrosis (41).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase of myocardial NHE1 mRNA, protein, and/or activity has been documented in response to pressure and volume overload (Baartscheer et al 2003;Marano et al 2004), hypertension (Camilion de Hurtado et al 2002;Cingolani et al 2003), ischemia, and reperfusion (for review, see Avkiran 1999;, myocardial infarction (Chen et al 2004), rapid left ventricular pacing (Aker et al 2004;Leineweber et al 2006), idiopathic dilated cardiomyopathy (Taniguchi et al 1996) and chronic end-stage heart failure (Yokoyama et al 2000).…”
Section: Nhe1 In Heart Failurementioning
confidence: 99%
“…Studies using different models of cardiac remodeling and heart failure demonstrated that NHE-1 inhibition improves heart performance, particularly ventricular dysfunction and hypertrophy (Yoshida and Karmazyn, 2000;Kusumoto et al, 2001;Cingolani et al, 2003;Marano et al, 2004). NHE-1 inhibitors have been shown to reduce the hypertrophic response to various extracellular stimuli in cul-tured cardiac cells (Hori et al, 1990;Yamazaki et al, 1998;Karmazyn et al, 2003).…”
mentioning
confidence: 99%